Automated Koos Classification of Vestibular Schwannoma - Kujawa, Aaron; Dorent, Reuben; Connor, Steve; Oviedova, Anna; Okasha, Mohamed; Grishchuk, Diana; Ourselin, Sebastien; Paddick, Ian; Kitchen, Neil; Vercauteren, Tom; Shapey, Jonathan (Frontiers in Radiology, 2022)
Objective: The Koos grading scale is a frequently used classification system for vestibular schwannoma (VS) that accounts for extrameatal tumour dimension and compression of the brain stem. We propose an artificial intelligence (AI) pipeline to fully automate the segmentation and Koos classification of VS from MRI to improve clinical workflow and facilitate patient management. Methods: Artificial neural networks were trained and tested based on manual tumour segmentations and ground truth Koos grades of contrast-enhanced T1-weighted (ceT1) and high-resolution T2-weighted (hrT2) MR images from subjects with a single sporadic VS, acquired on a single scanner and with a standardized protocol. The first stage of the pipeline comprises a convolutional neural network (CNN) which can segment the VS and 7 adjacent structures. For the second stage, we propose two complementary approaches that are combined in an ensemble. The first approach applies a second CNN to the segmentation output to predict the Koos grade, the other approach extracts handcrafted features which are passed to a random forest classifier. The pipeline results were compared to those achieved by two neurosurgeons. Results: Eligible patients (n=308) were pseudo-randomly split into 5 groups to evaluate the model performance with 5-fold cross-validation. The weighted macro-averaged mean absolute error (MA-MAE), weighted macro-averaged F1 score (F1), and accuracy score of the ensemble model were assessed on the testing sets as follows: MA-MAE=0.11±0.05, F1=89.3±3.0%, accuracy=89.3±2.9%, which was comparable to the average performance of two neurosurgeons: MA-MAE=0.11±0.08, F1=89.1±5.2, accuracy=88.6 ± 5.8%. Inter-rater reliability was assessed by calculating Fleiss’ generalized kappa (k=0.68) based on all 308 cases, and intra-rater reliabilities of annotator 1 (k=0.95) and annotator 2 (k=0.82) were calculated according to the weighted kappa metric with quadratic (Fleiss-Cohen) weights based on 15 randomly selected cases. Conclusions: We developed the first AI framework to automatically classify VS according to the Koos scale. The excellent results show that the accuracy of the framework is comparable to that of neurosurgeons and may therefore facilitate management of patients with VS. The models, code, and ground truth Koos grades for a subset of publicly available images (n=188) will be released upon publication.